Influence of amaranth and melon seeds on the nutritional composition of an energy bar - Zambrano Loor, Ángel; Muñoz Murillo, José (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Energy bars are considered a healthy food alternative due to the different properties attributed to them. The research aimed to evaluate the influence of amaranth and melon seeds on the nutritional composition of an energy bar intended for human consumption. A unifactorial design with three treatments T1 (45% amaranth, 15% melon seeds), T2 (30% amaranth, 30% melon seeds), T3 (15% amaranth, 45% melon seeds) was used to prepare the bars. energetic. Proximal analysis of protein, ash, fat, fiber, moisture, carbohydrates, and energy were performed on each of the formulations. A sensory evaluation of each of the treatments was carried out in which the attributes of smell, color, flavor, texture and general appearance were evaluated; A total of 20 untrained panelists were used for this. The results were analyzed with the statistical program InfoStat. The proximal analysis shows that the content of protein, ash and fiber was higher in the T2 treatment with a total of 11.03%, 12.59% and 13.43%, respectively. The fat, moisture and energy contents were higher in the T3 treatment with a total of 13.74%, 5.62% and 3820.85%. While the highest carbohydrate content was presented in treatment T1 with 67.14%. The evaluation of the organoleptic properties of taste, smell, color, texture and general appearance was better in the T3 treatment. The inclusion of the different levels of amaranth flour and melon seeds showed favorable results of the proximal and sensory characteristics (color, smell, flavor, texture and general appearance).